Cases of Halal Label Manipulation in The Food Industry: Analysis From The Perspective of Islamic Business Ethics - Wibisono, Anton; Mahrudin, Lintang Fajar (Bulletin of Management and Business, 2024)
This study aims to analyze, namely so that producers and consumers are aware of the importance of including halal labels and halal certification on every product they distribute in the community. This study uses a qualitative literature study method derived from various scientific works on the internet with a discussion that is in accordance with the author's theme. The results of this study indicate that producer awareness was initially very minimal and consumers also considered halal labels not very important. However, due to the large amount of socialization of halal life, they are aware of the importance of halal certification of food products. This study uses secondary data derived from studies on the theory of Islamic business ethics and cases of halal label manipulation that exist in the current era. This study looks at the relationship between halal labels on food as an effective means for consumers to sort halal food more easily and is a form of producer responsibility in doing business and protection for consumers.